Gender-based violence and efforts to address the phenomenon: Towards a church public pastoral care intervention proposition for community development in Zimbabwe - Magezi, Vhumani (HTS teologiese studies, 2019)
Gender-based Violence (GBV) is a huge concern in many African countries such as Zimbabwe despite the preventative and mitigatory interventions that have been proposed and implemented by various stakeholders. The interventions applied range from policies and programmes that are government initiated as well as those interventions by social actors such as non-government organisations and Faith-based Organisations (FBOs) like churches. Gender-based violence as a social structural issue is sustained and perpetuated by cultural norms, values and beliefs that are fed by patriarchy, among other things. To effectively respond to the situation, interventions should target multiple social levels, including policy, government officials’ attitudes, individual men and women, families, community leaders and structures and social institutions such as churches. Churches are a critical community social institution that could play a pivotal role in addressing GBV. To position churches as players on public issues such as GBV, the questions that emerge are: ‘What is the role of the church in a public problem such as GBV? How could churches conceive and perform a public ministerial role that addresses GBV?’ To respond to these questions, this article employs the idea of public pastoral care as a nexus that churches could utilise in performing a community and public role function in contributing towards addressing GBV. Firstly, the article sketches the context of GBV in Zimbabwe and the various efforts to address it. Secondly, it outlines the ambivalent role of churches in GBV. Thirdly, it conceptualises the notion of public pastoral care as an approach that could be employed by churches to address GBV. Lastly, it proposes some public practical approaches that could be employed in addressing GBV by churches.